Experimental Infection with bovine parainfluenza type 3 virus in mice: Aida Bara Allawe@ and Anton Sabri Al-Bana - Allawe, Aida Bara (The Iraqi Journal of Veterinary Medicine, 2015)
Four weeks old mice were used for experimental infection with isolated bovine parainfluenza type 3 virus. Mice were divided into three groups: The first group was infected by intracerebral route, the second group was infected by intranasal route and the third group was a control group. Experimental infection with isolated bovine parainfluenza type 3 virus in mice revealed that the isolated BPIV-3 was unable to kill 4 weeks old mice within 65 days when inoculated by intracerebral route, but isolated BPIV-3 was shown to kill (5 out of 10) 4 weeks old mice within 65 days when inoculated by intranasal route. There was no mortality in the control group within the same period. Two weeks old mice were used for experimental infection with isolated bovine parainfluenza type 3 virus and histopathological examination of infected organs was performed. Experimental infection of 2 weeks old mice by isolated BPIV-3 revealed that isolated BPIV-3 induced hydrocephalus after intracerebral inoculation. Histopathological examination for collected organs of BPIV-3 infected 2 weeks old mice (brain and lung) indicated histopathological changes were detected in comparison to non-infected collected organs. Virus was reisolated from infected brains of experimentally infected mice with locally isolated BPIV-3.